2017
DOI: 10.1017/s1751731116001221
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of behaviour in stabled draught horse foals fed diets with two protein levels

Abstract: The present work is aimed at evaluating the behaviour of Italian Heavy Draught Horse (IHDH) foals reared in semi-covered stables and fed two isoenergetic total mixed rations with different dietary protein levels (13.2% and 10.6% of CP on dry matter). The study was prompted by the restrictions for nitrate emissions in farms of the European Nitrate Directive. One suggested solution is to reduce dietary protein while maintaining normal performance and welfare, but there is a lack of literature in studies of horse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
2
2
1
Order By: Relevance
“…Furthermore, as the present study quantified time budgets and did not qualitatively assess the horses' behaviour, further studies evaluating stereotypical behaviours and social interactions under different husbandry conditions are essential to fully assess their welfare implications. Surprisingly, considering the geriatric and orthopedically challenged equine demographic, the mean overall time budget for movement of 19% in this study is on the upper end of the reported 4.1-19.1% range for domestic horses and higher than the 4.3-13.4% observed in free-ranging conspecifics [13,16,[23][24][25][26]36,[40][41][42][43][44][45]. The time budgets for movement can only be compared with caution due to differences in methodology, the low number of studies measuring the 24 h movement time budget in horses and the unclear distinction between foraging and movement in the few studies that did [1,13,66].…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Furthermore, as the present study quantified time budgets and did not qualitatively assess the horses' behaviour, further studies evaluating stereotypical behaviours and social interactions under different husbandry conditions are essential to fully assess their welfare implications. Surprisingly, considering the geriatric and orthopedically challenged equine demographic, the mean overall time budget for movement of 19% in this study is on the upper end of the reported 4.1-19.1% range for domestic horses and higher than the 4.3-13.4% observed in free-ranging conspecifics [13,16,[23][24][25][26]36,[40][41][42][43][44][45]. The time budgets for movement can only be compared with caution due to differences in methodology, the low number of studies measuring the 24 h movement time budget in horses and the unclear distinction between foraging and movement in the few studies that did [1,13,66].…”
Section: Discussioncontrasting
confidence: 71%
“…The overall time budget for resting of 39%, which included periods of inactivity and sleep, was higher compared to free-ranging conspecifics (12.9-29.3%) but well within the 15.6-66% range reported for domestic horses [13,16,[23][24][25][26]36,[40][41][42][43][44][45]. As horses divide their day mostly between eating and resting behaviour, the time budget for resting expectedly correlated negatively with eating (p < 0.0001, r = 0-0.655) and thus was highest in stabled (mean 47.97% ± 14.62% s.d.)…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The duration of lying, and with it the quality and length of sleep, is affected by various environmental influences, including the availability of a suitable lying area, space allowance, the presence and type of bedding, and lighting conditions [ 11 , 14 , 19 , 20 , 22 , 23 , 36 , 39 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Also, age influences the lying times with foals (up to 53.1% in domestic foals [ 10 ] and up to 15% in semi-feral foals [ 48 ]) and young horses (<2 years; up to 27% in domestic horses raised for meat production [ 49 , 50 ]; up to 8% in semi-feral horses [ 27 ]), who spend more time in recumbency than adults (3–15% in domestic and semi-feral horses [ 1 , 7 , 12 , 16 , 20 , 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 51 , 52 ]); however, the influence of old age on lying times has not yet been reported. In addition, painful conditions can modify lying times [ 4 , 18 , 53 , 54 , 55 , 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…The individual variation of the equine behavioral circadian rhythm requires detailed surveillance over several successive days [ 12 , 60 , 61 , 62 , 63 ]. However, to date, only a few studies, four in (semi-)feral and five in domesticated horses, measured recumbency times for a minimum of 24 continuous hours [ 12 , 24 , 25 , 26 , 27 , 28 , 29 , 48 , 49 , 50 ]. Recent advances in biotelemetry, and biologging, using wearable automated tracking equipment, provide increased objectivity and new opportunities to remotely quantify behavior at scales and temporal resolutions that were not previously possible [ 12 , 64 ].…”
Section: Introductionmentioning
confidence: 99%